2010
DOI: 10.1117/1.3516593
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of multispectral wide-field optical imaging modalities to maximize image contrast for objective discrimination of oral neoplasia

Abstract: Abstract. Multispectral widefield optical imaging has the potential to improve early detection of oral cancer. The appropriate selection of illumination and collection conditions is required to maximize diagnostic ability. The goals of this study were to (i) evaluate image contrast between oral cancer/precancer and non-neoplastic mucosa for a variety of imaging modalities and illumination/collection conditions, and (ii) use classification algorithms to evaluate and compare the diagnostic utility of these modal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 30 publications
1
35
0
Order By: Relevance
“…16 Roblyer et al used CPI to probe the diffusely reflecting light predominately coming from deep mucosal layers. 18,24 Though vascular contrast enhancement can be valuable, an inherent tradeoff of CPI is the loss of surface architecture due to the rejection of photons reflected off the tissue surface. Moreover, as the spatial resolution of white light imaging continues to improve through the development of higher-definition endoscopes, we must evaluate whether CPI would add a significant amount of information over those improvements.…”
Section: Discussionmentioning
confidence: 99%
“…16 Roblyer et al used CPI to probe the diffusely reflecting light predominately coming from deep mucosal layers. 18,24 Though vascular contrast enhancement can be valuable, an inherent tradeoff of CPI is the loss of surface architecture due to the rejection of photons reflected off the tissue surface. Moreover, as the spatial resolution of white light imaging continues to improve through the development of higher-definition endoscopes, we must evaluate whether CPI would add a significant amount of information over those improvements.…”
Section: Discussionmentioning
confidence: 99%
“…A study applied classification algorithms to compare various contrast features extracted from multispectral optical images and found that the ratio of red-to-green fluorescence intensity in a 405-nm excited autofluorescence image maximized the image contrast for the differentiation of neoplastic and non-neoplastic tissue. 8,10 In another study by the same authors, a computer program was developed to delineate the dysplastic area on the autofluorescence image over the white light image to increase the ability to identify the region. 21 In contrast, although 5-aminolevulinic acid (ALA) induced PpIX fluorescence has been reported to be able to overcome the limitations of autofluorescence in the differentiation between dysplasia and cancer, 17,22 the lack of comparison studies to evaluate the validity of the various image processing algorithms means that standard contrast enhancement methods are unavailable.…”
Section: Introductionmentioning
confidence: 99%
“…Two types of fluorescence indicators have been reported to be valuable: autofluorescence 5,[8][9][10][11][12][13] and protoporphyrin IX (PpIX) fluorescence. 6,[14][15][16][17][18] Previous studies have shown autofluorescence to reduce with oral malignancy; 5,9,10,19,20 however, this change is not easy to discriminate by visual inspection. A study applied classification algorithms to compare various contrast features extracted from multispectral optical images and found that the ratio of red-to-green fluorescence intensity in a 405-nm excited autofluorescence image maximized the image contrast for the differentiation of neoplastic and non-neoplastic tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the reported fluorescence systems use a commercial semiprofessional camera coupled to a UV light that provides the illumination of the investigated tissue. 6,[10][11][12][13][14][15][16][17][18][19][20] A longpass filter is placed before eye visualization or image registration to remove backscattered excitation photons. Fluorescence light can be detected by a CCD camera providing a three-scalar spectral image of the tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of commercial devices are already available in the USA. [22][23][24][25][26][27] Nowadays, new devices are proposing a combination of fluorescence with more techniques such as reflectance, 19 optical coherent tomography, 28 and fluorescence lifetime imaging. 29 It has to be pointed out that the majority of the studies performed until now still rely on clinical assessment by one or more doctors trained in this technique.…”
Section: Introductionmentioning
confidence: 99%